Contextual E-Comic Media to Enhance Elementary School Students’ Social Attitudes in Social Studies Learning - Mahartini, Komang Trisna; Tristananda, Putu Wulandari (Journal of Education Technology, 2025)
The low level of social attitudes among elementary school students—such as empathy, responsibility, and cooperation—remains a problem in Social Studies (IPS) learning across many schools. This study aims to develop contextual e-comic media in Social Studies to improve students' social attitudes. This research employed a Research and Development (R&D) approach using the ADDIE model, integrated with field testing stages from Borg & Gall. The research subjects included nine experts (in content, language, and graphic design), 12 fifth-grade students for small-scale trials, and 108 students for large-scale trials, including both experimental and control groups. Data were collected using validity questionnaires, practicality questionnaires, and social attitude questionnaires (pretest-posttest), supported by observation and user feedback. Data analysis was conducted using both qualitative and quantitative methods, including Aiken’s V, Ideal Theoretical Reference Assessment (PAIT), descriptive statistics, and ANOVA. The results showed that the contextual e-comic media had very high validity levels with Aiken’s V scores of 0.93 (content), 0.95 (language), and 0.90 (design). The small-scale practicality test yielded average scores of 4.87 (teachers) and 4.61 (students), while the large-scale test produced average scores of 4.76 (teachers) and 4.21 (students), all within the "highly practical" category. These findings indicate that the contextual e-comic media is highly feasible for use in Social Studies learning to effectively and enjoyably foster students’ social attitudes.